EXAMINING MULTIMODAL LEARNING AND PROJECT-BASEDPEDAGOGIES: IMPACT ON ACADEMIC ATTAINMENT AND 21ST CENTURY SKILLS IN SECONDARY EDUCATION - Loso Judijanto; Rerin Maulinda; Muhammad Ichsan Abda; Muhammadong; Suhana Sarkawi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This comprehensive investigation delved into the intricate relationship between multimodal learning environments and cognitive development, focusing on the impact of project-based pedagogies on academic attainment and the cultivation of 21st-century skills in secondary school learners. The study employed a systematic approach, analyzing diverse literature to synthesize empirical findings. The exploration revealed a positive nexus between project-based pedagogies and enhanced academic achievement, showcasing improved comprehension and practical application of subject matter. Additionally, integrating multimodal learning environments consistently correlated with developing essential 21st- century skills, including critical thinking, collaboration, communication, and adaptability. These insights contribute to a nuanced understanding of practical pedagogical approaches, emphasizing the significance of dynamic, project-based learning environments in shaping well-rounded learners in secondary education.